Weight Prediction of Cilembu Sweet Potato based on 2 Dimension Image Using Sorting Maching - Tika Hafzara Siregar; Setya Permana Sutisna; Tri Susilo; Salsabila Safha Mewavianti (Jurnal Rekayasa Lingkungan dan Biosistem, 2023)
Cilembu sweet potato is an agricultural product that is in great demand by the community. One of the processes carried out after harvesting is determining the weight of the cassava. This weight measurement is done to classify Cilembu sweet potato according to weight so that the selling price of the product can also be adjusted. Sorting by weight can be done using image processing methods. This method is more accurate than other sorting methods. The purpose of this study was to separate Cilembu sweet potato products based on weight using image processing methods. This study uses 2-dimensional image processing to determine the weight of Cilembu sweet potato. The results of this Cilembu sweet potato sorting machine research obtained the value of the linear regression equation x = (y – 10476) / 153.05 and the value of R-squared (R²) = 0.759 . The results of heavy testing have an average error of 7.62%. The standard deviation of the presentation error is 5.61.